Comparing chebyshev polynomials and adomian decomposition method in solving nonlinear volterra integral equations of second kind - Siti Aminah Mohamad Sapawi, 1990- author; Munira Ismail, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2014